(Re)considering New Agents: A Review of Labour Market Intermediaries within Labour Geography. Issue 4 (23rd April 2013) - Enright, Bryony
Abstract The world of work continues to change. Labour markets in most countries are increasingly shaped by policies of neoliberal deregulation while strategies of flexibility dominate public policy and corporate strategy across an array of sectors. At the forefront of these changes are the myriad labour market intermediaries that are used by workers and employees to enhance their ability to navigate ever more complex and volatile labour markets. For some, mediated employment, recruitment and work practices mean greater career progression and profit making ability, but for many others, it means increased precarity, vulnerability and insecurity. This paper critically reviews existing literature within geography on three types of private labour market intermediary, namely temporary staffing agencies and contract brokers; executive search firms and headhunters; and informal intermediaries such as gangmasters. The final section addresses the future for research in labour geography and, in particular, suggests new ways in which to broaden our understanding of labour market intermediaries and their impact on worker agency.